Heat transfer enhancement in fin channels using aeroelastically fluttering reeds. Issue 2 (19th December 2021) - Jha, Sourabh; Glezer, Ari; Realff, Matthew J.; Blaine, Miriam E.; Mai, Jiaqi; Pearlstein, Arne J.
Abstract: Forced convection heat transfer in rectangular channels is enhanced by aeroelastically fluttering thin reeds extending over the channel span. The resulting small‐scale vortical motions substantially increase local heat transfer at the channel walls and mixing between the wall thermal boundary layers and the channel's core flow. Mechanisms associated with evolution of these small‐scale motions and their thermal effects are experimentally studied in a channel of width W, span 5 W, and length 50 W . Reed effects on heat transfer are characterized at Reynolds numbers ( Re ) of 2000, 7000, and 12, 000 using embedded thermocouple arrays, and related to small‐scale motions by particle image velocimetry and hot‐wire anemometry. Reed‐induced small‐scale motions increase turbulent kinetic energy, increasing the global Nusselt number (by up to 145% at Re = 7000), with enhancement being sustained even when the base flow becomes fully turbulent ( Re = 12, 000). Enhancement is also demonstrated for fin arrays. Single‐reed computations show the effect of reed length on enhancement. Computations with two reeds, one downstream of the trailing edge of the other, predict heat transfer enhancement significantly greater than twice the single‐reed result, and point the way to use of a streamwise array of reeds in long channels. A techno‐economic analysis for an air‐cooled condenser suggests that fluttering reeds can be economically justified for a range of operating conditions.